A biomimetic nanoenzyme for starvation therapy enhanced photothermal and chemodynamic tumor therapy. Issue 45 (17th November 2020) - Xu, Keqiang; Wu, Xiaqing; Cheng, Yan; Yan, Jiao; Feng, Yanlin; Chen, Rui; Zheng, Runxiao; Li, Xi; Song, Panpan; Wang, Yanjing; Zhang, Haiyuan
Abstract : Glucose oxidase decorated N-doped carbon nanoparticles have been designed as a biomimetic nanoenzyme, which present prominent synergistic effects of starvation therapy enhancing photothermal therapy and chemodynamic therapy against tumors. Abstract : Photothermal therapy (PTT) and chemodynamic therapy (CDT) are promising therapeutic modalities with high specificity, however, a single therapeutic modality cannot maximize therapeutic efficacy. In the present study, glucose oxidase (GOx) was decorated on N-doped carbon (NC) nanoparticles (NPs) as a biomimetic nanoenzyme (NC@GOx NPs), which could promote starvation therapy enhanced PTT and CDT against tumors. GOx could decompose to cut off the supply of energy and nutrients, inducing starvation therapy, which further lowered adenosine triphosphate (ATP) levels, inducing downregulated heat shock proteins and creating a more suitable microenvironment for improving PTT efficacy. Meanwhile, the generated endogenous hydrogen peroxide (H2 O2 ) could be converted into hydroxyl radicals to attack cancer cells. In fact, in vitro and in vivo experiments demonstrated that NC@GOx NPs could effectively kill cancer cells and eliminate tumors. This design provides a strategy for synergistic cancer therapy by using biomimetic nanoenzymes.